MENINGKATKAN KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PEMBELAJARAN PBL DENGAN PENDEKATAN TARL PADA SISWA KELAS HETEROGEN - Cahya Resqueta, Mevianda; Oktavia Kartikasari, Nur; Fahimuddin, Alfian; Ekawati, Rooselyna; Mardiani, Ari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research reveals an improvement in mathematical problem-solving skills through the implementation of Problem Based Learning (PBL) model with the Teaching at the Right Level (TaRL) approach. The TaRL approach was chosen based on cognitive diagnostic test results showing significant differences between high and low-achieving students. Observations of student learning habits also identified passivity and reluctance to ask questions to teachers about unclear topics, which impacted their learning outcomes. In Cycle I, the researcher conducted planning, implementation, observation, and reflection stages. Students were grouped into three levels (high, medium, and low) based on diagnostic test results. These groups were used to distribute students heterogeneously within one group, with high-achieving students acting as peer tutors for others.The results from Cycle I showed improvement, with 19% of students achieving very high scores, 66% achieving high scores, and the rest achieving medium scores. In Cycle II, after modifying the teaching modules based on Cycle I results, there was a significant improvement in learning outcomes. There were no students with medium-level abilities, and most students achieved high or very high levels of proficiency. These results reflect an enhancement in mathematical problem-solving skills through the PBL model with the TaRL approach.